Peran FOMO (Fear of missing out) dalam Meningkatkan Kecemasan Terhadap Media Sosial pada Generasi Z - Muhamad Oldy Royantara; Agung Wijaya; Rini Sugiarti; Fendy Suhariadi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the role of Fear of Missing Out (FOMO) in increasing anxiety towards social media in Generation Z. FOMO, which is defined as an excessive fear of missing out on experiences or information felt by others, is one of the significant factors influencing the digital behavior of the younger generation. This study uses a qualitative approach with a phenomenological study method to explore in depth the experiences and perceptions of Generation Z related to Fear of Missing Out (FoMO) and its impact on anxiety in using social media. The results showed that Generation Z has a high level of FOMO, with the majority of respondents reporting excessive use of social media to follow trends, friends' activities, and viral content. This high FOMO has been shown to be positively correlated with increased anxiety, which includes feelings of excessive anxiety, difficulty focusing, and dependence on social validation through social media. These findings confirm that FOMO is a significant psychological challenge for Generation Z in the digital era. Therefore, efforts are needed to improve digital literacy, develop time management strategies in using social media, and create awareness about the impact of FOMO on mental health. This study makes an important contribution to understanding the impact of social media on Generation Z and provides a basis for more effective interventions.